Okay so here we have the function f(x)=3x-6 if you plug in -2 to x you get -12 if you plug in -1 you get -9 and if you plug in 0 you get -6 add three each time
Answer:
Step-by-step explanation:
To define the perpendicular line we need to first know the slope of the reference line graphed.
m=(y2-y1)/(x2-x1) we have points (0,5) and (2,1)
m=(1-5)/(2-0)
m=-4/2
m=-2
For lines to be perpendicular their slopes must satisfy
m1m2=-1, we have a line with a slope of -2 so
-2m=-1
m=1/2, so our perpendicular line is so far
y=x/2+b, it must have point (3,2) so we can solve for b
2=3/2+b
b=1/2, so the swimmer will travel along the line
y=x/2+1/2
Answer:
(3,2)
Step-by-step explanation:
Let's solve this via elimination method:
![\begin{cases} x+y=5\\x-y=1\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%20x%2By%3D5%5C%5Cx-y%3D1%5Cend%7Bcases%7D)
By subtracting equation 2 from equation one we obtain:
![\begin{cases} x+y=5\\-(x-y=1)\end{cases}\\\\0x+2y=4\\\\y=2](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%20x%2By%3D5%5C%5C-%28x-y%3D1%29%5Cend%7Bcases%7D%5C%5C%5C%5C0x%2B2y%3D4%5C%5C%5C%5Cy%3D2)
Next we can use any equation either 1 or 2 to determine what x is, I'll use equation 1. Let y=2 and so:
![x+y=5\\\\x+2=5\\x=5-2\\\\x=3](https://tex.z-dn.net/?f=x%2By%3D5%5C%5C%5C%5Cx%2B2%3D5%5C%5Cx%3D5-2%5C%5C%5C%5Cx%3D3)
Therefore the solution for the system of equations is:
x=3 and y = 2 as an ordered pair we have (3,2)
Answer:
12
Step-by-step explanation:
1. Substitute each letter with the numbers given
3(14) + 3(10) / 6
42 + 30 = 72 / 6 = 12